Preface - Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2012)
This special issue of CAMES contains eight papers, selected from 45 papers presented at the 2nd International Conference on Inverse Problems in Mechanics and Materials, called IPM 2011 for short, held in Rzeszów-Sieniawa, Poland on 27–30 April 2011. The conference continued the IPM 2009, organized in Rzeszów-Łańcut. These conferences were organized under the auspices of ECCOMAS as were the thematic conferences held in 2009 and 2011. The papers, collected in the special issue, correspond to various problems discussed at the IPM 2011. From the view point of engineering applications the papers can be subdivided into the following engineering problems: 1) detection and classification of damage in aluminum and composite strips; 2) structural damage of a 3D steel frame; 3) load carrying capacity of reinforced concrete columns; 4) residual stress fields reconstruction in rails; 5) parameter identification of electro-phonon coupling in a thin metal film, as well as heat conduction and solidification problems.